Metalloproteinases and Their Tissue Inhibitors in Comparison between Different Chronic Pneumopathies in the Horse - Ann Kristin Barton; Tarek Shety; Angelika Bondzio; Ralf Einspanier; Heidrun Gehlen (Hindawi Limited, 2015)
In chronic respiratory disease, matrix metalloproteinases (MMPs) contribute to pathological tissue destruction when expressed in excess, while tissue inhibitors of metalloproteinases (TIMPs) counteract MMPs with overexpression leading to fibrosis formation. They may be out of balance in equine pneumopathies and serve as biomarkers of pulmonary inflammation. We hypothesized that MMPs and TIMPs correlate to clinical findings and bronchoalveolar lavage fluid cytology in different equine chronic pneumopathies. Using a scoring system, 61 horses were classified controls as free of respiratory disease (n=15), recurrent airway obstruction (RAO, n=17), inflammatory airway disease (IAD, n=18), or chronic interstitial pneumopathy (CIP, n=11). Zymography and equine MMP and TIMP assays were used to detect MMP-2, MMP-8, MMP-9 as well as TIMP-1, and TIMP-2 in BALF supernatant. MMP-2, TIMP-1, and TIMP-2 concentrations were significantly increased in RAO and IAD compared to controls. MMP-9 concentration and MMP-8 activity evaluated by fluorimetry were significantly increased in RAO, IAD, and CIP. These results were confirmed by zymography for MMP-2 and MMP-9 activity in 52 horses. In conclusion, MMPs and TIMPs correlate well with clinical and cytologic findings. These findings support the usefulness of MMPs, TIMPs, and their ratios to evaluate the severity of respiratory disease and may help to identify subclinical cases.